Rendahnya Keikutsertaan Masyarakat dalam BPJS Mandiri - Wahyuningtyas, Fatma Ayu; Rahardjo, Bambang Budi (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Karanganom village has the lowest National Health Insurance in the form of BPJS health membership in the North Klaten Sub-district, which is around 8.563 people (80,9%) out of 10.583 people. The purpose of this study is to determine the factors that influence the low participation of the independent BPJS. Methods: The type of research is analytic observasional with a cross sectional research design. The sampling technique uses purposive sampling with inclusion and exclusion criteria. The sampel that will be analyzed is 99 respondents. The instrument is a questionnaire with questions for each research variable. The data were analyzed by chi square test and fisher’s test with the help of SPSS 21. Result: The results showed that there was a relationship between the level of education (p=0,007), level of knowledge (p=0,000), behavior (p=0,000), and social support (p=0,006). Where as employment (p=0299), total income (p=0,060), number of family members (p=0,170), socialization (p=0,592), information (p=0,214) are not related. Conclusion: The conclusion of this study is the level of education, level of knowledge, behavior, and social support related to community participation in independent BPJS.